Based Learning History Values of The Kingdom Sultanate of Bima (Bo Sangaji Kai) to Improve The Character Education Students in The District Bima - Muhammad Soalihin & Stveridan Yantus Neolaka (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
In this globalization era, the teaching of history in schools is increasing.This is due to the education at local and national level continue to beprepared evenly. Learning values-based history books of the ancientkingdom is a new breakthrough in the teaching of history. Thisbreakhthrough is useful for improving student character education inschools based on local wisdom. The goal is that the teaching of historybased on the values of the kingdom of Bima Sultanate book cancontribute to the development of student character education based onlocal wisdom. This study use research and development method to createproducts of learning. Products used in the form of models and learningmodules as well a manual for history teachers in the teaching of history.It is intended that teachers can meet the needs pf the teaching of historybased characters education. Learning values-based history book thiskingdom to foster a new spirit for student, so it has strong character tothe advancement of education at local and national levels.Keywords: Learning History, Values, Character Education